Mots négatifs dans les constructions comparatives en français et leurs équivalents en serbe - Vlahović, Ljubica (Vestnik za tuje jezike, 2017)
In French and Serbian comparative constructions of equality and inequality, negative words are distributed according to their forms, meanings and functions. French negative words - ne most frequently complemented by a particle pas or some other negative word, a double particle ni...ni, as well as negative ne and a double particle ni...ni in Serbian appear in the main clause (but not in the dependent clause) of comparative constructions of equality and inequality. In comparative constructions of inequality with a positive main clause, French expletive ne appears in the dependent clause with the verb, while its equivalent in Serbian nego or no occurs as a connector at the beginning of the dependent clause. Negative words in the main clause of comparative constructions of equality make the French antecedents flexible: the reduced form si alternates with aussi, as well as reduced tant with autant, and Serbian ones stable: reduced tako (from isto tako) and reduced toliko (from isto toliko) are mandatory. The autonomous word isto (easily detachable) serves to enhance the meaning of equality. The French comparative constructions of inequality with a negative main clause may have a dependent clause without or with an expletive ne, while the equivalent Serbian constructions always have a dependent clause with nego or no containing an expletive ne. There is a semantic and a functional equivalence between the French and Serbian constructions, with some syntactic differences due to the systems of two languages.
Keywords: francoščina; French; Serbian; srbščina; kontrastivna analiza; contrastive analysis; comparative construction; primerjalne konstrukcije; negative words; nikalne besede; nikalnice; negation; denial; zanikanje